Knowledge, Attitude, Practices, and Health Beliefs of Pregnant Women about Urinary Tract Infection and Its Associated Risk Factors: A Local Filipino Community Experience - Navarro, Annalyn; Tiongco, Raphael Enrique; Bundalian Jr., Reynaldo (Kesmas, 2019)
Urinary tract infection (UTI) during pregnancy is assumed to be associated with increased maternal and fetal morbidity and mortality; hence, a proper assessment of knowledge and practices is crucial to formulate preventive strategies to ensure the health of both the mother and the baby. The study determined the knowledge, attitude, practices (KAP), and the beliefs of pregnant women about UTI based on the Health Belief Model. A survey questionnaire was used to gather data from pregnant women with and without UTI. The association of the pregnant women’s sociodemographic characteristics with their KAP and health beliefs was determined using Pearson’s chi-square test. Results of the study showed that the majority of pregnant women have unsatisfactory knowledge with a positive attitude and good hygienic practices against UTI. Educational qualification and socioeconomic status showed a significant association with the KAP of pregnant women. Positive attitude and satisfactory hygienic practices were evident among the respondents despite their unsatisfactory knowledge. The salient traits of the Filipino women are exhibited on the descriptive of the Health Belief Model that include being resilient amid a problem and considering difficulties not as barriers but opportunities to make life healthier and better.